Comparison between zeolite and probiotic added in rabbit commercial diet in reducing ammonia concentration - Rusli, Izzuddin (2016)
Rabbit is one type of animal that been reared in our country as farm animal. Despites of their cuteness, rabbits will produce waste that includes urine, manure and residue. The amount of waste will be threatens to our health and animal's. Strong smells of ammonia can be nuisance to people. Hence, reduction concentration of the ammonia emission can help to decrease suffocating of smell to the animals and worker. On top of that, if the concentration of ammonia is too high, it may risks the health and cause several problem especially respiratory systems. In view of their, a measure to reduce ammonia emission from rabbit excretion can be done by diet formulation. Apart from this, it also help environment from being polluted. Therefore, the study was aimed to conduct an experiment on feed additive in rabbit diet to reduce the concentration of the ammonia. This experiment was compared three different treatments that are control (commercial rabbit feed), zeolite (commercial rabbit feed added with zeolite) and probiotic (commercial rabbit feed added with probiotic) in rabbit diet. Ammonia was collected by using badge sampler. There are two different points of badge samplers has been placed for each cages. The reason for placed it at different point because the ammonia may not get caught by the badge sampler if only has one point of badge sampler during collection time. The samplers were analyzed at the laboratory to determine the concentration of NH3. The results appeared these additions of zeolite and probiotic into the feeds had reduced the level of ammonia concentration. For example, at day 4 of sampling, means for control treatment showed 0.42 mg/L. Meanwhile, there is slightly reduced means in zeolite and probiotic treatments that are 0.39 mg/L and 0.36 mg/L respectively. Thus, there are significant different (p<0.05) between control treatment and probiotic treatment. Thus, hypothesis proven that zeolite and probiotic can be used to reduce ammonia.